Determining the electrical conductivity of rat cadaveric liver, spleen, and kidney to estimate early postmortem interval - Zhe Zheng; Xiandun Zhai; Zhiyuan Xia; Yaonan Mo (Wolters Kluwer Medknow Publications, 2017)
Previous research has found that electrical conductivity (EC), an important index to predict meat freshness and shelf life, is very promising for estimating the late postmortem interval (PMI). However, whether it has potential use in the early PMI has not been fully studied yet. To test this possibility in the present study, EC of three internal organs of rat liver, spleen, and kidney were determined within 24 postmortem hours, and then, EC changes at different PMIs were carefully analyzed. The overall results showed that EC of liver and spleen increased significantly with PMI while EC of kidney had minor changes during the same period. Specifically, significant linear positive correlations between EC of liver and spleen and PMI were found and the coefficients of their regression functions were R2 = 0.98 and R2 = 0.95, respectively. It can be concluded that determination of EC in certain internal organs such as liver and spleen may be a potential tool in the early PMI estimation. However, more researches on its influencing factors are needed to facilitate its final use in practice.